2020
DOI: 10.1039/c9py01627a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of double-responsive magnetic latex particles via seeded emulsion polymerization using macroRAFT block copolymers as stabilizers

Abstract: We report the synthesis of magnetic latex particles decorated with double-responsive PDMAEMA segments with fast magnetic response via RAFT-assisted emulsion polymerization, highlighting this strategy as a powerful tool for magnetic carriers design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…A promising technique to overcome this issue is based on the design of MNMs with high iron oxide nanoparticles encapsulated into polymer particles (functionalized by active groups). 12,13 Magnetic nanosorbents or magnetic polymeric nanoparticles (MPNPs) have been prepared by a wide range of techniques, including miniemulsion and seed emulsion polymerizations. [14][15][16][17] In our previous work, MPNPs selffunctionalized with carboxylic groups were fabricated via a miniemulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…A promising technique to overcome this issue is based on the design of MNMs with high iron oxide nanoparticles encapsulated into polymer particles (functionalized by active groups). 12,13 Magnetic nanosorbents or magnetic polymeric nanoparticles (MPNPs) have been prepared by a wide range of techniques, including miniemulsion and seed emulsion polymerizations. [14][15][16][17] In our previous work, MPNPs selffunctionalized with carboxylic groups were fabricated via a miniemulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, magnetic iron oxide nanoparticles such as magnetite (Fe3O4) or maghemite (γ-Fe2O3) have attracted great interest for a wide variety of different applications, from catalysis to bioengineering. Again, in most cases, their surface need to be functionalized to protect them from the surrounding environment and promote their dispersion in organic solutions or into polymer matrices [205][206][207][208]. Taking advantage of the high affinity of phosphonic acid groups for iron oxide surfaces, Matsuno and Takahara [201,209,210] reported the grafting of PS and poly(3-vinylpyridine) (P3VP) polymer chains from the surface of magnetite nanoparticles.…”
Section: Iron Oxidementioning
confidence: 99%
“…In our previous work, we demonstrated that the use of a crosslinker (namely, DVB) led to the encapsulation of IO clusters in a well-defined core-shell morphology. 49 In fact, for the system prepared in the absence of cross-linker in the monomer charge (100% styrene), the spherical clusters disassembled generating MLPs with a multi-encapsulated instead of a core-shell morphology. In the present work, seeded emulsion polymerization of styrene was thus first investigated using increasing amounts of DVB, while maintaining a fixed polymer content (PC theo = 12 wt%) and a fixed IO content (IOC theo = 10-11 wt%, based on overall monomer mass) (Exp.…”
Section: Synthesis Of Pdmaema-stabilized Magnetic Latex Particles (Pdmentioning
confidence: 99%
“…1, Table 1). The PDMAEMA@clusters were prepared as reported previously, 49 and exhibited a spherical shape with a number average diameter of 71 nm and a relatively large particle size distribution (D w /D n = 1.58, Table S2, ESI †). The suspension was purified by magnetic washing to remove non-adsorbed macro-RAFTs, and used as seeds in emulsion polymerization of styrene using DVB as a cross-linking agent ( Table 1).…”
Section: Synthesis Of Pdmaema-stabilized Magnetic Latex Particles (Pdmentioning
confidence: 99%
See 1 more Smart Citation